Analisis Penerapan 5S pada Laboratorium Kelistrikan Otomotif - Wibowo, Gigih; Iskandar, Ranu; Naryanto, Rizqi Fitri (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Efforts to create an orderly, efficient, and safe practice environment in vocational education laboratories require a standardized management system. This study examines the condition of the UNNES automotive electrical laboratory. This research aims to formulate a relevant and applicable laboratory improvement strategy. This research method uses 5S and SWOT analysis. This research is qualitative descriptive with observation stages, 5S audits, mapping findings, and strategic analysis. The audit results showed the weak implementation of the aspects of sorting, structuring, and work discipline, which had an impact on low efficiency and potential for practice safety. Through SWOT analysis, it was found that despite various internal weaknesses, there are still opportunities that can be used for the development of laboratory management systems. This combined approach produces a series of recommendations that can be implemented in the short and long term, and contributes to the development of sustainable governance of vocational education laboratories.